2020
DOI: 10.7150/ijms.46696
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate preconditioned Adipose-derived Stem Cells confer Neuroprotection in aging rat brain

Abstract: Aging is the most important current issue and is usually accompanied by complications, such as cardiovascular disorders and neurodegenerative diseases, which are the leading causes of death worldwide and the second major cause of death in Taiwan. In this study, we have investigated the protective effect of adipose-derived mesenchymal stem cells (ADSCs) and the role of epigallocatechin gallate (EGCG) in enhancing this effect in aging cerebral cortex of rats. Further, we attempted to elucidate the molecular mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Catechin is a phenolic active substance extracted from natural plants such as tea, comprising the active molecule epigallocatechin-3-gallate (EGCG) [ 105 ]. EGCG possesses anti-cancer, anti-obesity, anti-cardiovascular, neuroprotective, and other inherent properties [ [106] , [107] , [108] , [109] , [110] ]. Recent studies have suggested that EGCG also exerts effects against diabetes and its numerous complications, including diabetic nephropathy [ 111 ], peripheral neuropathy [ 112 ], diabetic retinopathy [ 113 ], and glucose tolerance [ 114 ].…”
Section: Effects Of Antidiabetic Drugs On Pcsk9mentioning
confidence: 99%
“…Catechin is a phenolic active substance extracted from natural plants such as tea, comprising the active molecule epigallocatechin-3-gallate (EGCG) [ 105 ]. EGCG possesses anti-cancer, anti-obesity, anti-cardiovascular, neuroprotective, and other inherent properties [ [106] , [107] , [108] , [109] , [110] ]. Recent studies have suggested that EGCG also exerts effects against diabetes and its numerous complications, including diabetic nephropathy [ 111 ], peripheral neuropathy [ 112 ], diabetic retinopathy [ 113 ], and glucose tolerance [ 114 ].…”
Section: Effects Of Antidiabetic Drugs On Pcsk9mentioning
confidence: 99%
“…Epigallocatechin‐3‐gallate (EGCG) is a bioactive polyphenol with antioxidant activity, found mainly in Camellia sinensis (green tea) 102 . This compound has been studied widely owing to its properties of preventing and reversing the damage caused by reactive oxygen species (ROS) 103,104 .…”
Section: Introductionmentioning
confidence: 99%